CRYSTAL VIOLET DYE BIOSORPTION AND PHYTOEXTRACTION USING LIVING SALVINIA NATANS AND SALVINIA NATANS POWDER: A COMPARATIVE STUDY - MÂNZATU, Carmen; NAGY, Boldizsár; TÖRÖK, Anamaria; SILAGHI-DUMITRESCU, Luminița; MAJDIK, Cornelia (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The main focus of this work was to investigate the biosorption behavior of living and powder Salvinia natans on Crystal violet (CV) removal. The effects of process parameters were studied in order to determine the optimum phytoremediation conditions. Adsorption isotherm and kinetic models for both processes were used to analyze the equilibrium data. It was found that Langmuir isotherm and pseudo-second-order kinetics models describe better the CV removal process. Thermodynamic parameters showed that the biosorption and phytoextraction process is endothermic. From the obtained results it can be concluded that S. natans powder showed higher bisorption capacity on CV removal compared to the living one.